Who Is Black : - Davis, F. James (Pennsylvania State University Press, 1991)
African Americans and white Americans have been inbreeding since the beginnings of slavery. Offspring of these matches were often defined by the "one-drop rule" (one drop of black blood made one black). Davis, a sociology professor, offers a well-researched history of this rule and its social and legal effects on the people of mixed race in America. Many were harassed by blacks because they were too light, while others tried to "pass" as white, ignoring the one-drop rule and, as a result, part of their heritage. Davis also compares the United States with other countries to see how they handled this issue. Though scholarly in tone, this fascinating book answers many questions but will leave readers with other questions that need to be answered. A definite addition to the available work on miscegenation and African American studies. For all academic libraries. Danna C. Bell-Russel, Marymount Univ. Lib., Arlington, Va.